The Influence of Instagram Content @MenjadiManusia.Id on Fulfilling Mental Health Information Needs - Sandwina, Farra Nastya; Kusmareza Adim, Adrio (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The recent surge in mental health cases is becoming a global issue, including in Indonesia. The increasing number of cases has prompted many to seek various solutions, such as the Instagram account @menjadimanusia.id, which focuses on sharing content related to mental health issues. This highlights the need for mental health information aimed at the public to address mental health problems. The purpose of this study is to determine the impact of the Instagram content from @menjadimanusia.id on meeting the need for mental health information. This study employs a quantitative research methodology by distributing questionnaires. The sampling technique used in the study is probability sampling, specifically simple random sampling with a sample size of 400 respondents. The results of the correlation coefficient test found a strong, significant, and positive relationship with a t-value of 18.961, which is greater than the t-table value of 1.660. The conclusion of the study is that there is a significant influence of Instagram content on meeting mental health information needs, accounting for 47.5%, while the remaining influence is attributed to other factors outside the scope of this study